Language strategies of the Enlightenment: the image of ʽPolandʼ in French Napoleonic Press - Kholtobina, Nelli (Poznańskie Studia Slawistyczne, 2018)
In this article, we reconstructed a generalized image of Poland and Poles within the framework of the multidisciplinary concept of “mental mapping”. The most popular daily newspaper of Napoleon’s time “Journal de l’Empire” (1804–1814) used distinctive linguistic markers of the Enlightenment to depict Poland and its inhabitants in French society, such as, “civilization”, “barbarity”, “culture”, “tradition” (“religion”), “childhood of nation”. Content analysis has been applied as an auxiliary method to the press sources which allowed to determine the nature and the impact of political propaganda on the public imagination.